A two LOM aplication profiles: for learning objects and for information objetcs - Vicente, Alfonso (2009)
Learning Objects are the central concept of the current paradigm of E-Learning, but curiously, there is still a widespread confusion about how much to include, how big should be, or what is the “correct” granularity for a Learning Object. Because of this, different works use the same term to different things. This paper attempts to differentiate the concepts of Learning Objects and Information Objects, and analyze the potential for achieving adaptivity in the two levels. Particularly, studying the design of two LOM application profiles for exploit the specifics of each level of granularity.